The Burden of Hypoxic Respiratory Failure in Preterm and Term/Near-term Infants in the United States 2011-2015 - Shivani Pandya; Onur Baser; George J. Wan; Belinda Lovelace; Jim Potenziano; An T. Pham; Xingyue Huang; Li Wang (Journal of Health Economics and Outcomes Research)
**Objectives:** This study quantified the burden of hypoxic respiratory failure (HRF)/persistent pulmonary hypertension of newborn (PPHN) in preterm and term/near-term infants (T/NTs) by examining health care resource utilization (HRU) and charges in the United States.